Sperm Quality in HIV-1 Seropositive Men under Antiretroviral Therapy at HIV Integrated Clinic of Dr. Ciptomangunkusumo Hospital, Jakarta, Indonesia - Margaretha Napitupulu (Journal of Global Pharma Technology, 2020)
The effect of human immunodeficiency virus (HIV) infection on male fertility as assessed by sperm quality is still in controversy in various studies. On the other hand, HIV seropositive men who are stable under the influence of antiretroviral therapy (ARV) experienced an increase in quality and life expectancy that allow them to have offspring. This study aims to investigate the sperm quality of HIV seropositive men in Indonesia. In addition, this study also compared sperm quality in HIV seropositive men who were stable under the influence of ARV (case group) with HIV seronegative men (control group). Semen samples from HIV seropositive male patients at the HIV Integrated Clinic, Ciptomangunkusumo Hospital, Jakarta, Indonesia were collected and analyzed for sperm in the laboratory, including: volume, pH, concentration, motility, morphology and sperm vitality. Comparison of sperm quality between the two groups was analyzed using independent t-test and Kruskal-Wallis test. Significant decrease in sperm quality was shown in the concentration, percentage of progressive motility and sperm vitality (p